TUTUR SRI AJI JAYA KASUNU: KAJIAN BENTUK, FUNGSI, DAN MAKNA - Gede Ariwangsa, Ida Bagus (Humanis; Volume 10. No 2. Februari 2015, 2015)
Efforts to explore the socio-cultural values is the purpose of this study, as well as problem-solving research Sri Aji Kasunu oracle forms in Balinese life, the said function in the lives of the people of Bali, and the meaning of the story in a particular social and cultural contexts associated with Hinduism. In this study using the theory of the structure and function to provide new interpretations of a text based on the assumption that the text is always live and thrive spawned ambiguous meanings or bring a lot of meaning, as well as the semiotic theory works in the communication process as a sign that the text should be interpreted readers. The results of research emphasize three aspects of form, function, and meaning. Said form of Sri Aji Jaya refers Kasunu story structure include; plot, characterization, setting, theme, and the mandate. Function in this speech relates to religious activity, and also provide insight and planting attitudes, mental, and moral society. While this meaning in speech emphasized on the understanding that the deconstruction of the text story has many possible meanings including; religious meaning and aesthetic meaning.
Keywords: speech, form, function, meaning.